(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study aimed to investigate the attributes of the ‘good nurse’ from patients’ and nurses’ perspectives in the literature. Method: A total of 11 studies were identified from literature search. The data relevant to the characteristics of good nurses was extracted and categorized into two subsets of personality traits and professional competence according to conceptual distinction. Finding: The characteristics of regardful, humanistic, supportive, and faithful were the most frequently identified personality trait of ‘good nurses.’ The attributes of professional manner, practical competence, patient-centered care, and communication were regarded as the essential professional competence for ‘good nurses.’ Improvements/Applications: The characteristics of ‘good nurses’ identified in this study, including not only the professional competence but also the personality traits, indicate the need to make comprehensive and balanced approach of nursing education for training ‘good nurses.’